Potential Analysis Of Toxoplasmosis Distribution In Wild Cats (Felis silvestris) In Some Markets Of Sidoarjo District Through Microscopic Identification Of Toxoplasma gondii - Rizal Zakaria; Syahrul Ardiansyah (Medicra (Journal of Medical Laboratory Science/Technology), 2020)
There are many diseases caused by parasitic infection, one of them is toxoplasmosis which is a zoonotic disease. This study was to determine the potential spread of wild cat toxoplasmosis in several markets. The sample used in this study were 24 stray cats taken from the Larangan market, Suko market and Sukodono market in Sidorajo district, using a method of determining the size of the sample based on incidental sampling. Sample were examined using the floating method.The prevalence result obtained from Larangan market (37,5%), Suko market (37,5%) and Sukodono market (12,5%). Prevalence result in Larangan market and Suko market greater than in Sukodono market, this is due to environmental factors in Sukodono market cleaner and better sanitation. Human can become infected with oocyst if they consume food or inhale particle contaminated with T.gondii parasites. High number of cat with oocyst T.gondii can be caused by a dirty environment.